Tribological Performances For Palm Kernel Activated Carbon Epoxy Composite - Mat Tahir, Noor Ayuma (2016)
Nowadays, it is expected that for most materials to be environmental friendly. Waste materials may be considered a secondary source of materials with an energetic advantage due to its high energy content. Consisting of a carbon material from agriculture wastes as new reinforcement substitutes in the fabrication of polymer matrix composites, are supposed to have large potential for a zero waste strategy in improving tribological properties at an affordable cost. Until today, based on our knowledge and from the literature review, there is no study regarding the potential of Palm Kernel Activated Carbon (PKAC) as solid lubricant in polymer matrix composites. Thus, a study on carbon materials from agriculture wastes has a great potential in tribological applications. The objectives of this study were to investigate the tribological performance of Palm Kernel Activated Carbon Epoxy composites and its wear mechanisms, and proposed wear and friction equations using Analysis of Variance (ANOVA). Basically, the composite were formed into pin shaped sizing of 30 mm height and 10 mm diameter using compaction technique. When the pin were ready, basic mechanical test were done. Then the pin were tested through pin-on-disc tribometer, then the surface morphology of the pin were studied through Scanning Electron Microscope (SEM) and Energy Dispersive Xray (EDX). The collected data were analysed through qualitative and quantitative approaches. From the study, it is interesting to find that the coefficient of friction and wear rate of the composite are highly affected by the composition and temperature due to the failure of the Epoxy bond. In addition, some traces of transfer layer were also found. Through comparison between friction and wear equations proposed with the experimental value, the equations shows average of 90.70% of reliability. Thus it can be said that the PKAC-E composite has high potential as the self-lubricating materials.